2019
DOI: 10.31384/jisrmsse/2019.17.2.7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lean Practices on Educational Performance: An Empirical Investigation for Public Sector Universities of Malaysia

Abstract: Education is considered the backbone of any country. Although Malaysia is a growing economy, this growth cannot sustain without education. In the last few decades, this factor has affected negatively, particularly due to the reduction in the budget; public sector universities have suffered significantly. However, various strategies and approaches are available in the literature that can help institutions to tackle the problems by improving efficiency and effectiveness. Lean management is considered as a crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This issue can badly affect performance because customers want their service to be fast and efficient. The increased workload can also affect employees' effectiveness, eventually affecting customer queuing time [15]. Therefore, to enhance service delivery in government, this study highlights the effect of LM implementation on public sector performance.…”
Section: Public Sector Performances: the Current Issuesmentioning
confidence: 94%
See 1 more Smart Citation
“…This issue can badly affect performance because customers want their service to be fast and efficient. The increased workload can also affect employees' effectiveness, eventually affecting customer queuing time [15]. Therefore, to enhance service delivery in government, this study highlights the effect of LM implementation on public sector performance.…”
Section: Public Sector Performances: the Current Issuesmentioning
confidence: 94%
“…In the offices, the workspace environment is essential in ensuring process efficiency. Nevertheless, the poor workspace due to the unnecessary or unorganised things (inventory) such as office supplies were criticised by recent studies [6,15]. Additionally, skill waste is about not using people's full abilities or giving them the wrong work or tasks that can cause a delay in the work process.…”
Section: Public Sector Performances: the Current Issuesmentioning
confidence: 99%
“…For instance, Testa, Nielsen, Bogers, and Cincotti (2019) suggest the adaptation practices in manufacturing firm are internal sustainable procedures that benefit the outside sustainable supply chain. Fedorova and Pongrácz (2019) have indicated that coordination between manufacturing firms and supply chain business partners, customers are high-order capabilities which rests on skills generated by the manufacturing procedures implemented by the firm (Shahbaz, Mubarik, Mubarak, & Irshad, 2019).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…There are many variables that deduce the incentive for manufacturing companies to greater involvement in SCSS. First, the propagation of sustainability values with a supply chain requires managerial efforts and additional cost from the focal firms (Shahbaz et al, 2019). For example, sub-tier suppliers are often situated in countries that do not require high environmental and social rules and principles, and the distance between institutional and geomorphic compounds becomes a problem in dealing with such relationships, (Das, 2017).…”
Section: Customer Satisfaction and Scssmentioning
confidence: 99%
“…This enables organizations to improve efficiency, agility, and innovation capabilities, leading to enhanced customer experiences and value creation (Lee et al, 2018;Mubarak et al, 2023). However, DT is not a onesize-fits-all solution, and its success depends on various factors such as organizational culture, leadership, and capabilities (Liu et al, 2020;Shahbaz et al, 2019;Mobashar and Mubarak, 2020).…”
Section: Digital Transformationmentioning
confidence: 99%